Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis IPAS di Sekolah Dasar - Ariawan, I Kadek Eno (Journal of Comprehensive Science, 2024)
Education in Indonesia faces great challenges in improving students' critical thinking skills, especially in Natural and Social Sciences (IPAS) subjects. Conventional teaching methods that are still widely used, such as lectures, often limit student engagement and reduce their ability to solve problems. This study aims to analyze the influence of the Problem Based Learning (PBL) model on students' critical thinking skills at SD Negeri 2 Dauh Puri. Using a qualitative approach with in-depth interview techniques, this study reveals that the application of PBL significantly improves students' critical thinking skills. Students become more active in learning, able to analyze problems in more depth, and collaborate in groups to find solutions. In addition, the PBL model also helps students relate the knowledge gained to real-life situations in everyday life. The discussion shows that PBL not only improves critical thinking skills, but also supports the development of 21st century skills such as creativity, collaboration, and communication. Thus, the implementation of PBL can be an effective solution in improving the quality of learning in elementary schools, preparing students to face future challenges, as well as strengthening important skills needed in daily life.